Plant-Based Formulas and Liquid Feedings for Infants and Toddlers - Yvan Vandenplas (MDPI AG, 2021)
Exclusive breastfeeding is the recommended feeding for all infants. Recent research has focused on the importance of balanced feeding during the first 1000 days, starting at conception with a balanced diet of the pregnant woman, up to the age of two years. The following step, a balanced diet after the age of two years is a challenge, as the dietary intake becomes more diversified. The role of young-child formula in this process is debated. This paper discusses the use of planted-based drinks, since they are a valuable and progressively more popular alternative for cow’s milk, if nutritionally adapted to the requirements of toddlers. Plant-based drinks are per definition lactose free.